Feeding ecology study of Asian redtail catfish, Hemibagrus nemurus (Teleostei: Bagridae), post-sediment flushing in Jenderal Soedirman Reservoir Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wibowo DN, Sukmaninggrum S, Widyastuti A, Soedibya PHT, Rahayu NL. 2024. Feeding ecology study of Asian redtail catfish, Hemibagrus nemurus (Teleostei: Bagridae), post-sediment flushing in Jenderal Soedirman Reservoir Central Java, Indonesia. Biodiversitas 25: 2315-2322. Hemibagrus nemurus Vallenciennes 1840 is among the valuable fisheries commodities in Banyumas District and led to high exploitation. Research on H. nemurus is essential for its conservation, including its feeding ecology. Feeding ecology studies of H. nemurus have been conducted previously, but the relative examination of this Asian redtail catfish is lacking in Jenderal Soedirman Reservoir, Central Java, Indonesia. Therefore, this study aimed to investigate the feeding ecology of H. nemurus, focusing on post-sediment flushing in the Jenderal Soedirman Reservoir in 2022. Specimens were collected at nine sampling sites in the reservoir during morning and evening sessions, with observed parameters including mouth position, intestine length ratio, intestine content, and the index of preponderance (IP). The results showed that H. nemurus had a subterminal mouth position as well as shorter to slightly longer intestines than the standard body length (SL). Based on the IP value, diets inside the intestine were dominated by animal materials, namely fish compounds. Hence H. nemurus seemed to be predatory considering its detected piscivorous habits. The identified mouth position, intestine length, and dominant diets were similar to the reports on the same species from other regions. These feeding ecology data would provide essential information for the fisheries and conservation of H. nemurus in Jenderal Soedirman Reservoir.